Cloning of a CHS gene of Poncirus trifoliata and its expression in response to soil water deficit and arbuscular mycorrhizal fungi - Liu, Zhen; Cheng, Shen; Liu, Xiao-Qing; Kuča, Kamil; Hashem, Abeer; Al-Arjani, Al-Bandari Fahad; Almutairi, Khalid F.; Abd_Allah, Elsayed Fathi; Wu, Qiang-Sheng; Zou, Ying-Ning (Frontiers in Plant Science, 2022)
Flavonoids are secondary metabolites widely found in plants with antioxidants, of which chalcone synthase (CHS) is a key enzyme required in flavonoid synthesis pathways. The objective of this study was to clone a CHS gene from trifoliate orange (Poncirus trifoliata) and analyze its biological information and partial functions. A PtCHS gene (NCBI accession: MZ350874) was cloned from the genome-wide of trifoliate orange, which has 1156 bp in length, encoding 391 amino acids, with a predicted protein relative molecular mass of 42640.19, a theoretical isoelectric point of 6.28, and a lipid coefficient of 89.82. The protein is stable, hydrophilic, and high sequence conservation (92.49% sequence homology with CHS gene of other species). PtCHS was highly expressed in stems, leaves and flowers, but very low expression in roots and seeds. Soil water deficit could up-regulate expressions of PtCHS in leaves. An arbuscular mycorrhizal fungus, Funneliformis mosseae, significantly increased plant biomass production, CHS activity, expressions of PtCHS, and total flavonoid content in leaves and roots, independent of soil water status. Total flavonoids were significantly positively correlated with PtCHS expression in leaves only and also positively with root mycorrhizal colonization. Such results provide insight into the important functions of PtCHS in trifoliate orange.